The potential of the typological study of ceramics. The example of “Etruria Padana” - Chiara Mattioli (Groma, 2016)
The desire to create a general typology of the ceramics produced locally in ‘Etruria Padana’ came out of the need to for systematic study the ceramics from the excavation of the ancient Etruscan town of Marzabotto (Bologna), abandoning the previous approach of sub-dividing materials according to the individual areas of excavation. Once the type was established, we carried out a comprehensive analysis of the ceramic forms found, with the intention of determining whether such production was sufficiently homogeneous to allow us to define "Etruscan regional production”. At the same time, particular attention was paid to anomalies and morphological differences in order to ascertain the existence of local characteristics, exclusive to certain territories.